Impacts of distributive comparison behavior on corporate social responsibility in supply chains: The role of small firms - WANG, Mingzheng (Institutional Knowledge at Singapore Management University, 2023)
Problem definition: In this paper, we explore how a firm’s concern about profit distribution and the size of downstream firms in supply chains affect corporate social responsibility (CSR) investment strategy. Methodology/results: In a supply chain consisting of one supplier and one manufacturer, both players decide whether to invest to reduce CSR violations, and they negotiate over a wholesale price. Distributive comparison behavior makes the manufacturer compare the profit with his equitable payoff, which is determined by the supplier’s profit. Advantageous (resp. disadvantageous) inequality occurs when the manufacturer’s profit is higher (resp. lower) than the manufacturer’s equitable payoff. We compare this supply chain to the one without distributive comparison behavior. We find that when advantageous inequality occurs, or when neither inequality occurs and the manufacturer’s sensitivity to the supplier’s profit is low, the manufacturer’s distributive comparison behavior makes the manufacturer less (resp. supplier more) likely to invest in CSR, which we call negative (resp. positive) impacts of distributive comparison behavior; otherwise, it makes the manufacturer more (resp. supplier less) likely to invest. In most cases, the weak bargaining power of the small manufacturer leads to larger positive or smaller negative impacts of distributive comparison behavior. Also, the low efficiency of the small manufacturer to reduce CSR violations leads to smaller negative impacts of distributive comparison behavior. Managerial implications: Our results show that governments and nongovernmental organizations (NGOs) should investigate firms’ distributive comparison behavior in supply chains. When downstream firms show the aversion to lower (resp. higher) profits than ones from upstream firms, the measures to monitor and support upstream (resp. downstream) firms’ CSR investments should be taken to avoid CSR violations. In the supply chains with small downstream firms, extra efforts should be made to induce firms’ distributive comparison behavior.